Appraisal of thermal comfort in rural household kitchens of Punjab, India and adaptation strategies for better health. (March 2019) - Ravindra, Khaiwal; Agarwal, Neha; Kaur-Sidhu, Maninder; Mor, Suman
Abstract: There is increasing evidence of adverse health impact of solid biomass fuel, and its use may hinder thermal comfort, which may lead to lower quality of life. Hence, current study aims to assess the thermal comfort at a rural location of Punjab, India. The indoor air temperature and relative humidity in rural households during winter varied from 11.9–25.2 °C and 63.4–90.5% respectively, during pre-summer it ranged between 21.3 and 27.4 °C and 48.4–78.4% while during summer it ranged between 28.4 and 37.8 °C and 13.7–63.8% respectively. The PMV of the households ranged between −0.85 to 0.69 (winter), −0.32 to 0.4 (pre-summer) and 0.53 to 1.25 (summer) for American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) 55-2017 and −0.56 to 1.11 (winter), 0.04 to 0.99 (pre-summer) and 1.21–2.36 (summer) for European Committee for Standardization (CEN) European standard EN15251 while the Predicted Percentage of Dissatisfied ranged between 5 and 20% (winter), 5–8% (pre-summer) and 11–38% (summer) for ASHRAE 55-2017 and 5–31% (winter), 5–26% (pre-summer) and 36–90% (summer) for EN15251 guidelines. On the other hand, Adaptive thermal comfort (ATC) during winter and pre-summer was comfortable for 80 and 90% acceptable limits (ASHRAE-2017) and ranged between too cool to comfortable for EN15251 (Class I, II and III) while during summer thermal comfort for occupants was comfortable for ASHRAE 2017 and EN15251 (Class I, II, III) but did not comply with EN guidelines in some households using either clean fuel or chullah. Thermal comfort sensation was observed to be slightly cool to neutral during winter, neutral during pre-summer and slightly warm during summer according to Predicted Mean Vote method. The results were also compared using a thermal comfort and household survey and found to be similar with the model results. Climate change is leading to changes in temperature which may have an impact on the built environment. Hence, the current study suggests formulating policies on the uses of household fuel and design of kitchen with proper ventilation to increase thermal comfort which in turn will also reduce air pollutants. Graphical abstract: Unlabelled Image Highlights: First study reporting the thermal comfort in rural households of India. PMV of rural households ranged between -0.32 to 1.25 as per ASHRAE 55-2017 standards Thermal comfort was observed slightly warm during summer months. SBF not only causes household air pollution but also affects the thermal comfort. Need to formulate policies to ensure adequate thermal comfort in households' microenvironments